EphB2 SNPs and sporadic prostate cancer risk in African American men. - Christiane M Robbins (PLoS ONE, 2011)
The EphB2 gene has been implicated as a tumor suppressor gene somatically altered in both prostate cancer (PC) and colorectal cancer. We have previously shown an association between an EphB2 germline nonsense variant and risk of familial prostate cancer among African American Men (AAM). Here we set out to test the hypothesis that common variation within the EphB2 locus is associated with increased risk of sporadic PC in AAM. We genotyped a set of 341 single nucleotide polymorphisms (SNPs) encompassing the EphB2 locus, including known and novel coding and noncoding variants, in 490 AA sporadic PC cases and 567 matched controls. Single marker-based logistical regression analyses revealed seven EphB2 SNPs showing statistically significant association with prostate cancer risk in our population. The most significant association was achieved for a novel synonymous coding SNP, TGen-624, (Odds Ratio (OR)  = 0.22; 95% Confidence Interval (CI) 0.08-0.66, p = 1×10(-5)). Two other SNPs also show significant associations toward a protective effect rs10465543 and rs12090415 (p = 1×10(-4)), OR = 0.49 and 0.7, respectively. Two additional SNPs revealed trends towards an increase in risk of prostate cancer, rs4612601 and rs4263970 (p = 0.001), OR = 1.35 and 1.31, respectively. Furthermore, haplotype analysis revealed low levels of linkage disequilibrium within the region, with two blocks being associated with prostate cancer risk among our population. These data suggest that genetic variation at the EphB2 locus may increase risk of sporadic PC among AAM.